THE USE OF CLARITY AND AMBIGIUTY IN ACADEMIC WRITING - Maripov Jalolkhan Kamoliddin o’gli; Bahramova Laziza A’zam qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the theory of  having  precise academic writing . However academic writing serves as fundamental means of communication  within the scholarly community , enabling  researchers , scholars, and students to convey complex ideas , present findings  and engage  with existing literature . However the balance between clarity and  ambiguity is precarious; effective academic writing must strive  for clarity while recognizing  that some level of ambiguity is often inherent  in complex ideas . This article shows the concepts  of clarity and  ambiguity and examines strategies for achieving a productive balance , and considers the implication for different academic disciplines  .